Acquirer size, political connections and mergers and acquisitions performance: Evidence from China. Issue 2 (19th June 2019) - Zhao, Xi; Ma, Huanyu; Hao, Ting
Abstract : Purpose: The purpose of this paper is to empirically examine the relationships between acquirer size and performance outcomes of the different process of acquisition in the Chinese context and the moderating effect of political connections on the size-performance relationship. Design/methodology/approach: Building upon agency theory, the paper examines the relationship between acquirer size and acquisition announcement returns to find whether the acquirer size effect exists in China. Moreover, the paper investigates whether large firms can perform better in the long run arising from scale economy. Finally, the paper examines the moderating effect of political connections on the size-performance relationship. Accounting for the complexity of political connections in China, the paper uses two methods to capture political connections. Findings: The paper finds that acquirer size plays a significant negative role on announcement returns, suggesting that the acquirer size effect also exists in China. However, acquirer size has a significant positive impact on long-term performance, indicating that large acquirers perform better in the integration process. Although no evidence shows that political connections can bring some off-setting benefits to acquirer size effect argued by Humphery-Jenner and Powell (2014), political connections, indeed, have a positive effect on mergers and acquisitions (M&As) announcement returns. Originality/value: The paper contributes to the corporate characteristic, political connections and M&A performance literature. Due to agency problem and scale economy, the effect of firm size on acquisition performance varies with the stage of M&A. Political connections can bring some benefits to M&A deals.